Rheology of natural and imitation mozzarella cheese at conditions relevant to pizza baking. (June 2016) - Berta, Marco; Muskens, Erwin; Schuster, Erich; Stading, Mats
Abstract: The rheology of mozzarella and imitation cheese was studied at 60 °C, with small amplitude oscillatory shear (SAOS), shear and extensional flow measurement at low strain rates in the range 0.01–1 s −1 . These conditions were chosen to replicate those experienced by the cheese during pizza baking and consumption. The extensional viscosity measurements were carried out by means of hyperbolic contraction flow, an alternative method to traditional extensional measurements. The extensional viscosity measured by hyperbolic contraction flow was related to the cheese elasticity and consequently to its stretchability, a major quality characteristic when this is consumed on pizza pies. The rheology of the two cheese materials could be explained by the structural observations made by confocal laser scanning microscopy (CLSM).